The Efficiency of Artificial Pollination on the Hazelnut ‘Tonda Francescana®’ Cultivar and the Xenia Effects of Different Pollinizers - Rodrigo José de Vargas; Simona Lucia Facchin; Chiara Traini; Nicola Cinosi; Fabiola Villa; Silvia Portarena; Marta Sánchez-Piñero; Mauro Brunetti; Angela Baiocco; Matteo Stabile; Daniela Farinelli (Horticulturae)
Pollination is a determining factor in achieving economic yield in hazelnut cultivation, and together with variable climate conditions, this requires the use of artificial pollination. This study evaluated the efficiency of artificial pollination performed with a manual sprayer using pollen from three pollinizer cultivars on the ‘Tonda Francescana®’ commercial orchard and the effect of different pollen sources on nuts. Dry pollens were applied by a Pollen Blower machine twice during female blooming. The pollen of ‘Nocchione’ determined the highest fruit set and yield per tree, even if it did not determine the highest blank seed percentage. The open pollinizers exhibited a lower sphericity and shape index (NSI), ‘Camponica’ pollen was associated with the biggest nut and kernel; ‘San Giovanni’ pollen showed higher nut elongation. Artificial pollination turned out to be a good tool to increase yield, but its efficiency is strongly influenced by the pollen used.